Pengaruh Brand Equity dan Brand Trust terhadap Loyalitas Pelanggan Teh Botol Sosro di Kota Bandung - Teguh Iman Basuki (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2017)
Currently the competition to attract consumers to use the product is no longer limited to promoting the initial functionality of a product but it will always be associated with the image of the product itself. The strength of a brand or brand Equity of a product is formed from the process of applying a good marketing strategy in shaping a brand while a product that is trusted by a consumer is a product that has a high brand trust because the product gives high satisfaction value to the consumer. This research is to know the influence of brand equity and brand trust to customer loyalty of Bottle Sosro Tea to Active Student of S1 STIE EQUITY STAFF STUDY 2011-2013, with member of population as much as 975 people, questionnaires distributed to 91 respondents by using error rate equal to 10%. The research method used is survey method, while data collection technique is done through interview and questionnaire. The analytical tool used is Line Analysis using IBM SPSS 20.0. The result of the research shows that there are significant positive influence either partially or simultaneously brand equity and brand trust to loyalty.